Possibility of recurring to ICT to improve learning differential calculation and decrease the dropout of students - Peña Chamorro, Libardo Ricaurte; Patiño Hernández, Luis Adolfo; Ordóñez, Dayner Felipe; Bravo Buchely, Alberto (SATHIRI, 2019)
The purpose of this research was to determine what criteria students and teachers have regarding the larning of differential calculus, having as support the ICT and specifically the Learning Objects (OA) to study the possibility of its implementation as part of a methodology that could contribute to decrease the dropout of this subject; research that was developed in the Agricultural Industries and Environmental Sciences Faculty (FIACA), of the Carchi State Polytechnic University (UPEC); and in the Computer Engineering Program at the University Institution Mayor del Cauca high school (IUCMC), computing career, on site modality; so that it can contribute to the improvement of learning of this science and in this way decrease the dropout. For which the theoretical framework aimed at reducing mechanistic behaviorism to move towards social constructivism and meaningful learning was found out. The theoretical methods used were analytical-synthetic; inductive-deductive; with these, the theoretical basis of the use of ICT in education and, in particular, the requirement of LOs to reduce attrition was obtained. The empirical method was used to collect information from students and teachers through the survey technique that operationalizes the independent and dependent variables, from which conclusions and recommendations are obtained.